Determinants of SMEs Non-Performing Loans in Commercial Banks in Sri Lanka: Special reference to Northern Province - Partheepan, N.; Yogendrarajah, R. (Sri Lanka Finance Association., 2023)
This study explores the determinants of non-performance advances (NPL) related to the small and medium enterprises (SMEs) sector in commercial banks in Sri Lanka that operate in the Northern Province. Institutional-related factors and borrower-related factors are the two main independent variables of this study. Furthermore, credit assessment, credit monitoring, and credit size were identified as variables of institutional-related factors; similarly, characteristics of the borrower and business management skills of the borrower are listed under borrower-related variables. Bank professionals are the sample of this study, and responses were obtained from 173 samples using the cluster random sampling method. A self-administrative questionnaire was used for the data collection, with a reliability Cronbach's alpha value of 0.862. The findings identified institutional-related and borrower-related factors that significantly impact SMEs NPL. Further, institutional-related variables of credit assessment and monitoring and borrower-related variables of the business management skills of the borrowers have a significant impact on SMEs NPL. Simultaneously, the institutional-related variables of credit size and the borrower-related variables of characteristics of the borrower have no significant impact on SMEs NPLs in commercial banks in the Northern Province. The study could be helpful to the country's lending unit's decision-makers and economic policymakers.
Keywords: Borrower-related factors; Credit assessment; Credit monitoring; Non- performing loan